Empowering Students’ Writing Skill through Performance Assessment - Suastra, I Made; Menggo, Sebastianus (Universitas Negeri Makassar, 2020)
It is quite common to our understanding that classroom assessment outcomes are not sensitive to the goal of teaching and learning language skills. More specifically, the assessment cannot allow the students to present what they know and what they are supposed to do. The purpose of classroom assessment is to inform teaching and to improve learning. Performance assessment gives the students a chance to demonstrate their knowledge and absorb a wide variety of information on language teaching and learning activities. This study aims to analyze the implementation of performance assessment in improving students' writing skills and disclosing the students' psychological factors on implementing performance assessment in the writing learning process. This is a descriptive qualitative study that was carried out for three months, namely October-December 2018. The participants of the research were 28 English department students of Udayana University. The instruments used were writing rubric, questionnaires, and interviews.Â These data were analyzed with the assistance of the excel chart data series software program and then followed by qualitative interpretation. The questionnaire data were displayed in the form of a percentage, while the data from the interviews were narrated in detail based on students' responses. The findings of the study reported a positive impact on students' writing skills (the mean post-test result = 78), boosts students' interest and awareness (92,85%), self-esteem (85,71%), and their motivation (78,57%). The practitioners are expected to implement performance assessment in enhancing students to be a competent English writer.